2014
DOI: 10.1155/2014/464781
|View full text |Cite
|
Sign up to set email alerts
|

Oncological and Functional Outcome after Surgical Treatment of Early Glottic Carcinoma without Anterior Commissure Involvement

Abstract: Introduction. Glottic carcinoma can be successfully diagnosed in its early stages and treated with high percentage of success. Organ preservation and optimal functional outcomes could be achieved with wide array of surgical techniques for early glottic cancer, including endoscopic approaches or open laryngeal preserving procedures, making surgery the preferred method of treatment of early glottic carcinoma in the last few years. Material and Methods. Prospective study was done on 59 patients treated for Tis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…13 Given the direct relationship between PPE and PTP, it can be concluded that patients with symptomatic AGW display an increase in PTP as the degree of occlusion increases. 14 …”
Section: Introductionmentioning
confidence: 99%
“…13 Given the direct relationship between PPE and PTP, it can be concluded that patients with symptomatic AGW display an increase in PTP as the degree of occlusion increases. 14 …”
Section: Introductionmentioning
confidence: 99%
“…Along with radiotherapy, transoral laser surgery (TLM) is one of the reference treatments for early glottic carcinoma . TLM offers excellent oncologic and functional results without the requirement of a lengthy hospital stay. The extent of tissue removal is a major issue as underestimation of the disease because of limited visualization or inadequate exposure of the lesion may lead to treatment failure .…”
Section: Introductionmentioning
confidence: 99%